RISIKO SOSIAL, PENDIDIKAN, DAN KESEHATAN AKIBAT PERNIKAHAN DINI PADA REMAJA PESISIR DI KEPULAUAN MUNA SULAWESI TENGGARA - Taherong, Rosmawati; Husniah, Wa Ode; Ulfa, Maria; Sabitri, Nanang; Rindi, Rindi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Early marriage remains a persistent social issue in coastal areas of Indonesia, including Tapi-Tapi Village, Muna Islands, where the Bajo community constitutes a significant social group. This phenomenon is not merely driven by limited access to education or the absence of succe ssful role models, but is more strongly influenced by free social interacti on among adolescents, weak self-control, and short-term thinking in interpreting intimate relationships and future life planning. This communi ty service program aimed to enhance adolescents’ psychological understa nding of the risks of early marriage, provide mental health education related to stress, anxiety, and depression, and develop adolescents’ personal skills to better prepare them for future life challenges. The program was implemented through psychosocial counseling, participat ory discussions, and community-based mentoring involving adolescents, parents, and local leaders. The results indicate an increase in adolesce nts’ critical awareness of the psychological and social consequences of early marriage, shifts in perceptions of the body and intimate relationsh ips, & strengthened reflective capacity in decision-making. Program underscores that preventing early marriage requires a non-repressive approach prioritizes psychosocial readiness & the strengthening of adole scent agency, rather than relying solely on normative/ moralistic control.